AeU Insights - Webinar 1: New Learning in the New Normal - Asia e University, AeU (2020)
If necessity is the mother of inventions, and given the plethora of pessimism, AeU proposes to consider a few encouraging possibilities to resolve the new learning via virtual learning. It is not as simple as using Zoom, Skype, Webex or Face Time, etc as new ways of on-line learning, but requires the articulation of innovative pedagogical skills and the deeper understanding of the learners, who are digital savvy than the instructors.